Impact of congested match schedules during the COVID-19 pandemic on technical and physical performance in the Chinese Super League - Yang, X.; Liu, Z.; Xu, Z.; Li, B.; Yu, Y.; Zhou, C. (International Journal of Performance Analysis in Sport, 2025)
This study examined the impact of fixture congestion on technical and physical performance in the 2021 Chinese Super League, which used a tournament-style format due to COVID-19. A total of 173 matches were analysed, including 116 congested (3-4 days between matches) and 57 non-congested (=5 days). Technical and physical indicators were collected via the AMISCO tracking system. Mixed-effects models showed that congested schedules enhanced passing indicators, including Passes (SE = 11.93, p = 0.039), Pass Accuracy (SE = 0.66, p = 0.012), and Forward Pass Accuracy (SE = 0.80, p = 0.028). However, defensive actions such as Challenges (SE = 1.11, p < 0.001), Aerial Challenges (SE = 0.93, p < 0.001), Tackles Won (SE = 1.29, p = 0.034), and Fouls (SE = 0.44, p = 0.041) decreased. Physical performance also declined, with reductions in Sprint Number (SE = 1.81, p < 0.001) and Sprint Distance (SE = 40.48, p < 0.001). These findings highlight significant effects of congested schedules, characterised by improved passing but reduced defensive and sprint performance. Coaches can consider optimised tactical adjustments and recovery strategies to minimise these impacts and sustain player performance under congested conditions.